Desferrioxamine B, an Inhibitor of Escherichia coli Motility, Reversing the Stimulating Effect of Cyclic Adenosine 3′,5′-Monophosphate - Maruyama, Hiromi B. (1975)
A substance inhibiting Escherichia coli motility was isolated by “motilometry” assay from the culture broth of Streptomyces sp. strain NR9GG8 and was found to be identical with desferrioxamine B. Its inhibitory effect was reversed by cyclic adenosine 3′,5′-monophosphate (cAMP), while the motility stimulation by cAMP was diminished by this inhibitor. Its effects on various enzymes involved in cAMP metabolism of function of cAMP were examined.